Environmental Education in Elementary School with Kamiholo: Kamishibai and Hologram as Teaching Multimedia - Hernawan, A. H.; Septiana, A. I.; Rachman, I.; Darmawan, D.; Kodama, Y. (Jurnal Pendidikan IPA Indonesia, 2022)
In environmental education, there have been many studies on learning multimedia, but the media used tends to be limited to the use of conventional media. In this study, we investigate the feasibility of Kamiholo, a combination between hologram and Kamishibai for environmental education in elementary school to improve the students' learning outcomes. To avoid bias and increase objectivity, the learning outcomes of Kamiholo utilization will be compared with those of conventional Kamishibai utilization. The experiments in the control and experimental groups both show good results. However, there is a significant difference in the improvement of the student achievement when learning using Kamiholo based on the N-Gain, where the N-Gain value of Kamiholo and Kamishibai are 0.69 and 0.49, respectively. Overall, we have successfully demonstrated the advantages of our new multimedia by combining holograms and Kamishibai for environmental education.